Comparison of two modelling strategies for 2D large-scale flood simulations. (December 2021) - Dazzi, Susanna; Shustikova, Iuliia; Domeneghetti, Alessio; Castellarin, Attilio; Vacondio, Renato
Abstract: In this paper, two emerging strategies for the reduction of the computational time of 2D large-scale flood simulations are compared, with the aim of evaluating their strengths and limitations and of suggesting guidelines for their effective application. The analysis is based on two state-of-the-art raster flood models with different governing equations and parallelization strategies: PARFLOOD, a GPU-accelerated code that solves the fully dynamic shallow water equations, and LISFLOOD-FP, which combines a parallel implementation for CPU with simplified equations (local-inertial approximation). The results of two case studies (a river flood propagation, and a lowland inundation) suggest that, at coarse grid resolutions, the parallelized simplified model LISFLOOD-FP can represent a good alternative to fully dynamic models in terms of accuracy and runtime, while the GPU-parallel code PARFLOOD is more efficient in case of high-resolution simulations with millions of cells, despite the greater complexity of the numerical scheme. Highlights: Long runtimes of 2D hydraulic simulations require effective speed-up strategies. Emerging models exploit parallelization or simplification of shallow water equations. The LISFLOOD-FP and PARFLOOD codes are compared as regards accuracy and runtimes. At high-resolution, PARFLOOD outperforms the simplified parallel LISFLOOD-FP. For coarse grids, LISFLOOD-FP is a good alternative to a more complex model.